Palestinian refugees and identity : nationalism, politics and the everyday - Achilli, Luigi (New York : I. B. Tauris, 2015)
Explores the everyday lives of the Palestinian refugees in Jordan, finding that there is a relative absence of political activity in the camps even though they feel an affinity for many of the meanings, ideals, and values of Palestinian nationalism.
It feels like home -- Imperatives of work -- Politics and Islam -- Ordinary masculinities --Time off!'Loitering' in the camp.
Includes bibliographical references (page [238]-249) and index.
Keywords: Refugees, Palestinian Arab -- Jordan; Refugees, Palestinian Arab -- Ethnic identity; Refugees, Palestinian Arab -- Political activity -- Jordan; Refugees, Palestinian Arab -- Jordan -- Social conditions